Planet friendly home-grown school feeding: What does it mean? - Borelli, Teresa; Nekesa, Tabitha; Mbelenga, Emiliana; Jumbale, Mwarome; Morimoto, Yasuyuki; Bellanca, Raffaella; Jordan, Irmgard (2024)
School meals present a unique opportunity to tackle the various food system challenges, including the depletion and pollution of natural resources, habitat and biodiversity loss, deforestation, ocean acidification, and climate change, while delivering multiple social and economic benefits towards sustainable food systems for healthy diets (WHO 2022; Pastorino et al. 2023).